SYSTEMATIC MAPPING OF PERFORMANCE ASSESSMENT RESEARCH: BIBLIOMETRIC STUDY WITH VOSVIEWER - Purwayadi, Teguh (Advances in Social Sciences Research Journal, 2020)
This article aims to find a map of the development of research on performance assessment. The study was conducted by searching through the Scopus database with the keyword performance assessment. The data from the search results are then analyzed descriptively based on the year of publication, the country that published the performance assessment research, and the focus of the research. To obtain a map of research development, the data from the Scopus database is exported into a Comma Separated Values ​​(CSV) file format, then processed and analyzed using the VOSViewer application program to find out the bibliometric map of the development of performance assessment research. The results of the systematic mapping conducted show that the trend of performance assessment research publications indexed in Scopus from 2011 to 2020 has fluctuated. The trend based on the country that published the most articles was the United Kingdom with 77 articles. The research topic that is mostly done is the study of performance measurement with 32 articles. Then, through VOSViewer visualization, it shows that the map of the development of performance assessment research is divided into 5 clusters, namely; Cluster 1 consists of 6 research topics, namely assessment, efficiency, evaluation, performance, public service, and sustainability; Cluster 2 consists of 5 research topics, namely balanced scorecard, benchmarking, data envelopment analysis, performance assessment, and performance indicators; Cluster 3 consists of 5 research topics, namely accountability, Canada, governance, performance measurement, and public management; Cluster 4 consists of 4 research topics, namely local government, performance management, public administration, and public sector reform; Cluster 5 consists of 3 research topics, namely job satisfaction, performance evaluation, and the public sector.